2013
DOI: 10.1177/1060028013504082
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dexmedetomidine and Propofol for Conscious Sedation in Awake Craniotomy

Abstract: Either DEX or PRO can be effectively and safely used for conscious sedation in awake craniotomy. Comparing the two, DEX produced a shorter arousal time and a higher degree of surgeon satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 30 publications
(61 reference statements)
2
57
0
1
Order By: Relevance
“…In another study, similar effects were reported with Dexmedetomidine and Propofol (Ünsal et al, 2004). Findings of the study was in line with the results of (Banihashem, SalehiOmran, & Jalalian, 2015) (Shen et al, 2013), (Wang, Shi, Qin, Zhou, & Xia, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…In another study, similar effects were reported with Dexmedetomidine and Propofol (Ünsal et al, 2004). Findings of the study was in line with the results of (Banihashem, SalehiOmran, & Jalalian, 2015) (Shen et al, 2013), (Wang, Shi, Qin, Zhou, & Xia, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, 50-100 ml/h of normal saline is provided intravenously. Dexmedetomedine has been extensively examined recently as a substitute for propofol to provide conscious sedation due to its positive effects, such as sedation without respiratory depression and a shorter arousal time [27].…”
Section: In the Operating Roommentioning
confidence: 99%
“…All of these have been discussed in the literature. 15,16,24,31,32,35 The first two of these techniques have previously been applied at the Department of Neurosurgery, University Hospital of Münster. Given recent publications, we decided to maintain the nomenclature "conscious sedation."…”
mentioning
confidence: 99%